Stratospheric connection to the abrupt end of the 2016/2017 iberian drought - Ayarzagüena, B.; Barriopedro, D.; Garrido‐Perez, J. M.; Abalos, M.; de la Cámara, A.; García‐Herrera, R.; Calvo, N.; Ordóñez, C. (Geophysical Research Letters, 2018)
Southwestern Europe experienced extraordinary rainy and windy conditions in March 2018, leading to the end of the most severe drought since 1970 at continental scale. This anomalous weather was linked to a persistent negative North Atlantic Oscillation pattern. Two weeks earlier a sudden stratospheric warming (SSW) took place, preceded by the strongest planetary wave activity on record. In this study, we explore the connection between the SSW and the weather shift by employing a weather regime approach and flow analogues. The timing of the downward propagation of the stratospheric anomalies, the transition to and persistence of the negative North Atlantic Oscillation weather regime, and the sudden precipitation increase are all consistent with the typical tropospheric state after SSWs. Our results evidence a significant role of the 2018 SSW in the record‐breaking precipitation event. Universidad Complutense de Madrid European Research Council Ministerio de Economía y Competitividad Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub